2008
DOI: 10.1074/jbc.m708188200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cyclin L1 and L2 Interactions with CDK11 and Splicing Factors

Abstract: Although it has been reported that cyclin L1␣ and L2␣ proteins interact with CDK11 p110 , the nature of the cyclin L transcripts, the formation of complexes between the five cyclin L and the three CDK11 protein isoforms, and the influence of these complexes on splicing have not been thoroughly investigated. Here we report that cyclin L1 and L2 genes generate 14 mRNA variants encoding six cyclin L proteins, one of which has not been described previously. Using cyclin L gene-specific antibodies, we demonstrate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
141
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 33 publications
7
141
0
5
Order By: Relevance
“…Cyclin L2 and the closely related isoform, cyclin L1 (originally named cyclin L) differ from all other members of the cyclin family by the presence of a C-terminal RS domain. The RS domain is a hallmark of many proteins involved in pre-mRNA progression of the cell cycle and the signal transduction of apoptosis and oncogenesis (Graaf et al, 2004;Yang et al, 2004;Loyer et al, 2008). In the present study, we observed that overexpression of human cyclin L2 have direct anti-proliferative effects on BCG823 cells, and also able to induce cellular apoptosis in vitro.…”
Section: Discussionsupporting
confidence: 59%
“…Cyclin L2 and the closely related isoform, cyclin L1 (originally named cyclin L) differ from all other members of the cyclin family by the presence of a C-terminal RS domain. The RS domain is a hallmark of many proteins involved in pre-mRNA progression of the cell cycle and the signal transduction of apoptosis and oncogenesis (Graaf et al, 2004;Yang et al, 2004;Loyer et al, 2008). In the present study, we observed that overexpression of human cyclin L2 have direct anti-proliferative effects on BCG823 cells, and also able to induce cellular apoptosis in vitro.…”
Section: Discussionsupporting
confidence: 59%
“…The closest paralogs of CDK10 within the CDK family are the CDK11 proteins, which interact with L-type cyclins (15). Interestingly, the closest paralog of these cyclins within the cyclin family is cyclin M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…No cyclin partner for Cdk10 has been identiWed so far; however, this kinase seems to be involved in regulating the G2-M phase by inhibition of Ets2 transactivation (Kasten and Giordano 2001). Cdk11 binds to CyclinL and is involved in mRNA splicing (Loyer et al 2008). It can also interact with CyclinD and repress proliferation (Duan et al 2010).…”
Section: Introductionmentioning
confidence: 99%